IBM Permainan Mencocokkan Gambar pada Lansia dengan Gangguan Fungsi Kognitif di Rumpelsos Lansia Pucanggading Semarang - Novita Wulan Sari; Margiyati Margiyati; Nanang Nanang; Rania Nabila (Jurnal Pengabdian Ilmu Kesehatan, 2025)
STIKES Kesdam IV/Diponegoro as a higher education institution in the health sector has great potential in contributing to the development of the assisted area, especially through community service in the health sector. Based on the results of interviews with the Division in Charge of the Elderly at Rumpelsos Pucanggading, it is known that most of the elderly experience a decline in cognitive function that has an impact on their quality of life and independence. Managing cognitive impairment in the elderly requires a sustained and stimulation-based approach, such as picture-matching game activities, music therapy, gardening, and spiritual activities. As a form of promotive and preventive intervention, the STIKES Kesdam IV/Diponegoro community service team carried out cognitive stimulation activities through a game of matching pictures to the elderly at Rumpelsos Pucanggading. This activity is designed to stimulate the memory, concentration, and thinking skills of the elderly in a fun and interactive way. Seniors are actively involved in game sessions tailored to their abilities and interests. The results of the activity showed that the elderly responded positively to the games given, with increased participation, enthusiasm, and the ability to recognize and remember images. This intervention is considered effective in helping to maintain and improve the cognitive function of the elderly in a simple but meaningful way. This activity also strengthens the role of universities in supporting community health through educational and humanistic approaches. It is hoped that similar activities can be carried out in a sustainable manner and developed with a variety of other stimulation methods, so as to be able to have a wider impact in maintaining the quality of life of the elderly and preventing progressive decline in cognitive function.